DINII BAGRIKENGLIKNING IZHTIMOIY POTENTIALS - Жамолиддин Тоғаймуродов (Galaxy International Interdisciplinary Research Journal, 2023)
Religious tolerance has a significant social potential. In a society that accepts this idea and is able to apply it appropriately to various aspects of its life, there will be fundamental qualitative changes not only in the social and spiritual, but also in the economic and political spheres. This is evidenced by the current experience of societies where religious tolerance is legally enshrined as an important principle of social relations. Of course, the social potential of religious tolerance can be interpreted and described in different ways. However, an analysis of its most basic aspects also makes it possible to show how incomparable its social significance is.